2021
DOI: 10.1126/scisignal.abg4747
|View full text |Cite
|
Sign up to set email alerts
|

Activation of PPARα enhances astroglial uptake and degradation of β-amyloid

Abstract: A drug combination turns neuroinflammatory astrocytes into neuroprotective, amyloid-clearing cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 61 publications
0
35
0
Order By: Relevance
“…Next day corresponding secondary antibody tagged with specific fluorophore (1:10,000; Jackson Immuno-Research) and the blots were scanned under Odyssey infrared scanner (Li-COR, Lincoln, NE). Band intensities were quantified using ImageJ software (NIH, USA) [ 38 40 ].…”
Section: Methodsmentioning
confidence: 99%
“…Next day corresponding secondary antibody tagged with specific fluorophore (1:10,000; Jackson Immuno-Research) and the blots were scanned under Odyssey infrared scanner (Li-COR, Lincoln, NE). Band intensities were quantified using ImageJ software (NIH, USA) [ 38 40 ].…”
Section: Methodsmentioning
confidence: 99%
“…In AD, PPARα is involved in the regulation of beta-secretase (BACE-1), an enzyme responsible for the cleavage and later formation of Aβ plaques, and studies have shown a significant downregulation of PPARα in AD pathology ( Wójtowicz et al, 2020 ). Furthermore, treatment with the PPARα agonist gemfibrozil together with retinoic acid (GFB-RA) was recently shown to lower amyloid plaque burden, improve memory, and reduce astrogliosis in mice ( Chandra and Pahan, 2019 ; Raha et al, 2021 ). These effects appear to be mediated by astrocytes through lysosomal biogenesis and autophagy pathways ( Raha et al, 2021 ), although alternative mechanisms of PPAR-regulated activity, such as molecular transrepression, may also be involved ( Ricote and Glass, 2007 ; Pawlak et al, 2014 ).…”
Section: Treatment Strategies Targeting Diet and Lipid-signaling Casc...mentioning
confidence: 99%
“…Furthermore, treatment with the PPARα agonist gemfibrozil together with retinoic acid (GFB-RA) was recently shown to lower amyloid plaque burden, improve memory, and reduce astrogliosis in mice ( Chandra and Pahan, 2019 ; Raha et al, 2021 ). These effects appear to be mediated by astrocytes through lysosomal biogenesis and autophagy pathways ( Raha et al, 2021 ), although alternative mechanisms of PPAR-regulated activity, such as molecular transrepression, may also be involved ( Ricote and Glass, 2007 ; Pawlak et al, 2014 ). GFB-RA has also been shown to stimulate two succeeding neuroprotective pathways that result in the degradation of beta-amyloid plaques.…”
Section: Treatment Strategies Targeting Diet and Lipid-signaling Casc...mentioning
confidence: 99%
See 2 more Smart Citations